Moving Toward an Agenda on Ocean Health and Human Health in Europe - Borja, Angel; White, Mathew P.; Berdalet, Elisa; Bock, Nikolaj; Eatock, Claire; Kristensen, Peter; Leonard, Anne; Lloret, Josep; Pahl, Sabine; Parga, Mariluz; Prieto, Julia Vera; Wuijts, Susanne; et al. (Frontiers in Marine Science, 2020)
The integrated study of ocean health and human health is an emerging area of increasing global importance. Growing evidences demonstrate that the health of the ocean and the health of humans have always been and will continue to be, inextricably linked. Our actions towards the oceans will significantly influence the future of the whole planet and, in turn, our own health. The current review of these issues arose from a summer school in San Sebastian (Spain), from 5th-7th June, 2019. An interdisciplinary group of researchers discussed key risks (e.g. microbial pollution, pharmaceuticals, harmful algal blooms, plastic pollution) and benefits (e.g. bathing waters, recreation, tourism) of the seas and global ocean for humanity; and debated the future priorities and potential actions for a joint Oceans and Human Health research and governance programme in Europe. The aim of this review is to contribute to the emerging scientific agenda on ocean health and human health, as well as coordinate efforts with stakeholders, policy makers and the general public. This agenda operates within the larger context of the upcoming United Nations Decade of Ocean Science for Sustainable Development: 2021-2030, which strives to achieve the Sustainable Development Goals (SDG), including healthy (human) lives and well-being (SDG3) and conserving and sustainably using the oceans (SDG14), among others. In addition to summarising some of the key risks and benefits, therefore, we describe the governance of oceans and health interactions (especially in Europe), and we finish by proposing a list of elements for potential future research priorities on oceans and human health.